2021
DOI: 10.1021/acs.orglett.1c00010
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening/Site Selective Cleavage in N-Acyl Glutarimide to Synthesize Primary Amides

Abstract: A LiOH-promoted hydrolysis selective C−N cleavage of twisted N-acyl glutarimide for the synthesis of primary amides under mild conditions has been developed. The reaction is triggered by a ring opening of glutarimide followed by C−N cleavage to afford primary amides using 2 equiv of LiOH as the base at room temperature. The efficacy of the reactions was considered and administrated for various aryl and alkyl substituents in good yield with high selectivity. Moreover, gram-scale synthesis of primary amides usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The main obstacle originates from the strong resonance stabilization effect in amides, which makes most amide C–N bonds too stubborn to be cleaved . In this wise, Lewis acid additives (Al, Sc, Ti, Zr, Fe, and others) or transition metal catalysts , or transition-metal-free protocols have been introduced to trigger the transamidation of amides, especially the tertiary ones (Scheme a). However, the reactions either proceed with incomplete conversion or require very high temperatures or specifically activated substrates .…”
Section: Introductionmentioning
confidence: 99%
“…The main obstacle originates from the strong resonance stabilization effect in amides, which makes most amide C–N bonds too stubborn to be cleaved . In this wise, Lewis acid additives (Al, Sc, Ti, Zr, Fe, and others) or transition metal catalysts , or transition-metal-free protocols have been introduced to trigger the transamidation of amides, especially the tertiary ones (Scheme a). However, the reactions either proceed with incomplete conversion or require very high temperatures or specifically activated substrates .…”
Section: Introductionmentioning
confidence: 99%
“…The NBO analysis of the neutral compound confirmed that the nitrogen, as well as the carbon atom of the amide moiety, are sp 2 -hybridized. The nitrogen atom possesses one lone pair, occupied with 1.74 e À , which is available for contributing to planar amidic bond resonance (n N !π* C=O conjugation), [5,23] which is illustrated in Figure 7. According to the NBO calculations, the oxygen atom reveals sp-hybridization.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…45 Recognizing that selective C–N bond cleavage in activated amide is a necessary process, 46,47 we established the synthesis of primary amide via hydrolysis in base or acid medium. 48,49 Yet, the highly reactive sensitive functional groups (esters or nitriles) undergo hydrolysis eventually which corresponds to substantial difficulties in chemoselectivity under basic or acidic medium which is considered to be a contemporary challenge. Practical and new catalytic methods for synthesizing primary amides in a simple, efficient, and eco-friendly manner are in major demand in pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%